(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the current research is to reveal the skills of solving physical problems among students of the fifth vocational grade and their relationship to their mental capacity, the research sample consisting of 200 male and female students of the second grade of vocational education has been selected at the state industrial schools in the district of Mosul Governorate. A physical problem-solving skills test was built into 23 items divided into five physical problem-solving skills, a ready-to-measure measure of mental capacity was selected and the psychometric properties of the two tools were verified, the research tools applied to the specified sample at the end of the first course of the 2020/2021 academic year, and under the supervision of the researchers. After analysing the results, it became clear that there was a high and positive correlation between physical problem solving skills and mental capacity in the second vocational students, and that gender had an impact on the level of physical problem solving skills and mental capacity scores and for the benefit of females. In the light of the results of the research, a number of recommendations and suggestions were made.